Search for Long-Range Correlations in Relativistic Heavy-Ion Collisions at SPS Energies - Shakeel Ahmad; Anisa Khatun; Shaista Khan; A. Ahmad; M. Irfan (Advances in High Energy Physics)
Long-range correlations are searched for by analysing the experimental data on 16O-AgBr and 32S-AgBr collisions at 200 A GeV/c and the results are compared with the predictions of a multi phase transport (AMPT) model. The findings reveal that the observed forward-backward (F-B) multiplicity correlations are mainly of short range in nature. The range of F-B correlations are observed to extend with increasing projectile mass. The observed extended range of F-B correlations might be due to overall multiplicity fluctuations arising because of nuclear geometry. The findings are not sufficient for making any definite conclusions regarding the presence of long-range correlations.